Desain Buku Sebagai Media Informasi Mengenai Menstruasi Pertama - Abeba, Ghea Syalsabila; Maulina, Rini; Nasruddin, Merlina Fatimah (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
This research aims to evaluate the effectiveness of books as information media in educating teenagers about first menstruation. The research methods used included questionnaires, interviews, and observations of a sample of teenage girls. The research results show that books are an effective source of information in helping teenagers understand their first menstruation. Teens who use books as a source of information tend to have a better understanding of the physical and emotional changes associated with menstruation. Apart from that, books also help reduce the stigma and anxiety related to menstruation. These results have important implications for the development of more effective adolescent health education programs. This study provides valuable insight into the role of books as a relevant information tool in understanding first menstruation.